The impact of supply chain disruptions on business expectations during the pandemic - Brent H. Meyer; Brian C. Prescott; Xuguang Sheng (Federal Reserve Bank of Atlanta, 2023)
Using the Federal Reserve Bank of Atlanta's Business Inflation Expectations (BIE) survey, which has been continuously collecting subjective probability distributions over own-firm future unit costs since October 2011, we document two facts about firms' marginal cost expectations and risk during the COVID-19 pandemic. First, in the early months of the pandemic, firms, on net, saw COVID-19 largely as a demand shock and lowered their one-year-ahead expectations. However, as the pandemic wore on, firms' one-year-ahead unit cost expectations rose sharply alongside their views on supply chain and operating capacity disruptions. Second, the balance of unit cost risks shifted sharply over the course of the pandemic, and by the end of 2022, upside risks had sharply outweighed perceived downside risks during the year ahead. We find that both positive demand shocks (for example, large order backlogs) and negative supply shocks (such as long supplier delivery times and labor shortages) have contributed to elevated short-term unit cost expectations and risk. Specifically, supply shocks accounted for roughly 40 percent of the increase in manufacturers' and nearly onethird of service-providers' unit cost expectations.
Keywords: E31; E32; 330; business expectations; COVID-19; demand shock; inflation; pandemic; supply shock